2011
DOI: 10.1097/aap.0b013e318228c33a
|View full text |Cite
|
Sign up to set email alerts
|

Value of Single-Injection or Continuous Sciatic Nerve Block in Addition to a Continuous Femoral Nerve Block in Patients Undergoing Total Knee Arthroplasty

Abstract: A single-injection or continuous sciatic nerve block in addition to a femoral nerve block did not influence time-to-discharge readiness. A single-injection sciatic nerve block can reduce severe pain on the day of the surgery, whereas a continuous sciatic nerve block reduces moderate pain during mobilization on the first 2 postoperative days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 33 publications
(24 reference statements)
2
73
0
Order By: Relevance
“…1), eight of which were published between January 1998 and March 2015 and met the eligibility criteria. 16,19,21,28,[38][39][40][41] One published abstract 17 was excluded for lack of outcome results after contacting its authors. Five trials that compared SNB with various analgesic modalities, but lacked an appropriate FNB control group, were also excluded.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1), eight of which were published between January 1998 and March 2015 and met the eligibility criteria. 16,19,21,28,[38][39][40][41] One published abstract 17 was excluded for lack of outcome results after contacting its authors. Five trials that compared SNB with various analgesic modalities, but lacked an appropriate FNB control group, were also excluded.…”
Section: Resultsmentioning
confidence: 99%
“…We subsequently evaluated the contribution of these characteristics to the heterogeneity of the results using subgroup analysis. Because evidence suggests that continuous SNB (i.e., catheter-based infusion via a pump) prolongs the duration of SNB analgesia, 16 we hypothesized that catheter use would introduce significant heterogeneity into our results. Consequently, we planned to analyze the outcome data separately according to whether single-shot sciatic nerve block (SSNB) or continuous sciatic nerve block (CSNB) had been used.…”
Section: Definition Of Relevant Outcome Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, numerous studies have compared the efficacy of various types of neuraxial anesthetics and peripheral blocks [1,7,23,28,31,37,38]. The addition of a sciatic block to a femoral block provides better pain relief than femoral block alone, and various combinations have been studied [4,7,10,17,37]. However, we were unable to find any study directly comparing this commonly used combination of a continuous femoral block given with a single-shot sciatic block with that of a periarticular injection.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have shown that periarticular injections provide improved pain relief compared with no injection [6,22,36]. Additionally, numerous studies have compared the efficacy of various types of neuraxial anesthetics and peripheral blocks [1,7,23,28,31,37,38]. The addition of a sciatic block to a femoral block provides better pain relief than femoral block alone, and various combinations have been studied [4,7,10,17,37].…”
Section: Introductionmentioning
confidence: 99%